2018
DOI: 10.1021/acs.jpcc.8b03280
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Response of Photoluminescence in Cesium Lead Iodide Perovskite Nanocrystals

Abstract: In this paper, we address the phase stability and the relationship between optical gap and structural perturbations in cesium lead halide nanocrystals. We report photoluminescence (PL) spectra for cesium lead iodide (CsPbI3) perovskite nanocrystals under hydrostatic pressures up to 2.5 GPa. The peak position of the CsPbI3 PL shifts as a function of pressure. Initially, the PL shifts to lower energies, until a reversal occurs near 0.33 GPa. At higher pressures, the PL peak position shifts to the blue until PL v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 47 publications
2
72
2
Order By: Relevance
“…4a , inset). The pressure response is different from that observed in CsPbI 3 perovskite nanocrystals where the PL at first shifted to lower energies below 0.4 GPa and then to higher energies with further compression 38 , 39 . These differences could be caused by the different structures and particle sizes of the samples.…”
Section: Discussioncontrasting
confidence: 78%
“…4a , inset). The pressure response is different from that observed in CsPbI 3 perovskite nanocrystals where the PL at first shifted to lower energies below 0.4 GPa and then to higher energies with further compression 38 , 39 . These differences could be caused by the different structures and particle sizes of the samples.…”
Section: Discussioncontrasting
confidence: 78%
“…To carry out this calculation we use the pressure deformation potential for CsPbI3 nanocrystals measured in the literature 35 of αp = 1.4×10 -2 eV/GPa. We note that the pressure deformation potential and the volume deformation potential are related through the bulk modulus, B = -VdP/dV, as shown in Eq.…”
Section: ≡ = (S23)mentioning
confidence: 99%
“…[52] Recently, Becker et al showed the lowest triplet exciton for CsPbX 3 is bright, which explains the anomalously fast emission rates for these materials compared to other semiconductors. [58] Raino and coworkers observed suppressed blinking and a fast decay from lowtemperature (6 K) photoluminescence measurements of CsPbCl x Br 3-x nanocrystals. [56] Both transition metals [35,57] and rare earth metals [34] have been doped into CsPbX 3 , achieving quantum yields greater than 60 % and 170 %, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Beimborn et al studied the effect of pressure-induced deformation on the photoluminescence, which leads to a fully reversible blue shift with decreasing intensity. [58] Raino and coworkers observed suppressed blinking and a fast decay from lowtemperature (6 K) photoluminescence measurements of CsPbCl x Br 3-x nanocrystals. [53] In contrast, Diroll et al studied high temperature photoluminescence of CsPbX 3 nanocrystals (up to 550 K), showing reversible photoluminescence loss below 450 K for CsPbBr 3 (the highest threshold among the compositions studied).…”
Section: Introductionmentioning
confidence: 99%